Channelling feedback through audiovisual presentations: Do higher education students perceive, use and benefit from video feedback compared to written feedback? - Máñez, Ignacio; Skrobiszewska, Noemi; Descals, Adela; Cantero, María José; Cerdán, Raquel; García, Óscar Fernando; García‐Ros, Rafael (Journal of computer assisted learning, 2024)
Background Delivering effective feedback to large groups of students represents a challenge for the academic staff at universities. Research suggests that undergraduate students often ignore the Elaborated Feedback (EF) received via digital learning environments. This may be because instructors provide feedback in written format instead of using more engaging channels (e.g., audiovisual). Objectives This quasi‐experimental study examines the extent to which feedback format (video vs. written) influences students' perceptions of feedback, their decision to access EF messages related to high‐stakes assignments in digital environments, and its impact on academic performance, while considering the effect of their academic engagement. Methods A total of 171 undergraduate students received generic EF messages through a learning platform the day after submitting each course assignment. 78 students received EF in written format and 93 in video format. Results and Conclusions Our results showed that feedback format influenced students' decision to access EF and their academic performance, but not their feedback perceptions. Students in the written‐feedback group accessed EF messages more often, but students who received video‐feedback performed better than their counterparts in the written‐feedback group. Moderation analysis showed that the relationship between the feedback format and students' academic performance was moderated by their academic engagement, suggesting that students with lower levels of academic engagement may benefit from video‐feedback. Takeaways The results reveal that using video feedback in digital environments may influence students' decisions to process EF and their academic achievement, especially when it comes to students with lower levels of academic engagement. Lay Description What is currently known about the subject matter Delivering Elaborated Feedback (EF) to large groups of students represents a challenge for instructors. Undergraduate students often ignore the EF received via digital learning environments. Students usually prefer audiovisual formats to receive feedback compared to the written format. Results in regard to whether video‐feedback is best for learning are inconclusive. What this paper adds A quasi‐experimental study to compare two feedback formats (video and written) in an ecologically valid setup. Data of students' voluntary decisions to process EF related to high‐stakes assignments. The moderating effect of students' academic engagement on the relationship between feedback format and academic performance. The implications of study findings for practitioners Students positively value the EF received in both video and written formats. Students may not engage with EF as expected even when provided in audiovisual formats. Students may access written‐EF more frequently than video‐EF. Video‐EF may positively influence academic performance when students have low levels of academic engagement.